Phase I study of cord blood‐derived natural killer cells combined with autologous stem cell transplantation in multiple myeloma. (14th March 2017) - Shah, Nina; Li, Li; McCarty, Jessica; Kaur, Indreshpal; Yvon, Eric; Shaim, Hila; Muftuoglu, Muharrem; Liu, Enli; Orlowski, Robert Z.; Cooper, Laurence; Lee, Dean; Parmar, Simrit; et al.
Summary: Multiple myeloma (MM) is a disease with known immune dysregulation. Natural killer (NK) cells have shown preclinical activity in MM. We conducted a first‐in‐human study of umbilical cord blood‐derived (CB) NK cells for MM patients undergoing high dose chemotherapy and autologous haematopoietic stem cell transplantation (auto‐HCT). Patients received lenalidomide (10 mg) on days −8 to −2, melphalan 200 mg/m 2 on day −7, CB‐NK cells on day −5 and auto‐HCT on day 0. Twelve patients were enrolled, three on each of four CB‐NK cell dose levels: 5 × 10 6, 1 × 10 7, 5 × 10 7 and 1 × 10 8 CB‐NK cells/kg. Ten patients had either high‐risk chromosomal changes or a history of relapsed/progressed disease. There were no infusional toxicities and no graft‐versus‐host disease. One patient failed to engraft due to poor autologous graft quality and was rescued with a back‐up autologous graft. Overall, 10 patients achieved at least a very good partial response as their best response, including eight with near complete response or better. With a median follow‐up of 21 months, four patients have progressed or relapsed, two of whom have died. CB‐NK cells were detected in vivo in six patients, with an activated phenotype (NKG2D + /NKp30 + ). These data warrant further development of this novel cellular therapy.